PERBEDAAN PENILAIAN KEADILAN KARYAWAN DITINJAU DARI JENIS KELAMIN - Nuqul, Fathul Lubabin (EGALITA, 2009)
Percieve of justice is most important factor to support an employ’s activ- ity. Percieve Justice has influenced to health, organization commitment, job satisfaction and productivity. In fact most discrimination toward women employees has accurs. But, teoritically, women are more tolerant than men in injustice situation. It is cause in our society has sex role, has derived what kind behaviors that does by women and men. The result of the study, reveal significant gender effect was non-existent.Key words: Keadilan, Karyawan, Jenis Kelamin